Substrate Integrated Waveguide Bandpass Filter dengan Complementary Split Ring Resonator - Dian Widi Astuti; Muslim Muslim; Trya Agung Pahlevi (Universitas Syiah Kuala, 2019)
Substrate integrated waveguide (SIW) is a technique to implement waveguide into microstrip material that can be applied to filter, antenna, mixer, coupler, and so on. Implementation of SIW to filter can overcome the problem of size reduction and high insertion loss commonly used in a conventional filter. While the complementary split ring resonator (CSRR) method overcomes the problem of size reduction and selectivity in conventional filters, thus combining the two can provide better filter performance. This research proposes both methods in realizing a bandpass filter by using a parameter study. Bandpass filter design works on a frequency of 3.4 – 4.6 GHz with an insertion loss value of 0.5 dB and a return loss value above 15 dB and has one transmission zeros at the frequency of 3.32 GHz. While the measurement results provide an insertion loss value below 3 dB and 6.5 dB return loss.